KOMPLEKSITAS POSKOLONIAL DALAM PUISI “NYANYIAN LAWINO” KARYA OKOT P’BITEK - Tatang Iskarna (Sunan Kalijaga State Islamic University Yogyakarta, 2011)
This article discusses how an African woman faces the postcolonial complexity as presented in the poem “Song of Lawino” (1966), written by Okot p’Bitek, an Uganda writer. The postcolonial complexity here means the difficult situation of decolonizing process as a result of a cultural clash between local African and Western culture, which has been internalized by some African people. The internalization of the Western culture creates self-hatred racism of African people, political group dispute, woman oppression, and mimicry. Using postcolonial perspective, which is proposed by Franz Fanon, Aime Caesar, and Homi K. Bhaba, the writer analyzes how this poem portrays three phenomena of postcolonial complexity. This postcolonial complexity is investigated through the conflict and the characters in the poem.